PENINGKATAN KEMAMPUAN MEMAHAMI PERISTIWA DETIK-DETIK PROKLAMASI MELALUI METODE BERMAIN DRAMA PADA SISWA KELAS VIID SMPN 7 PENAJAM PASER UTARA - Mardiana Piliang (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Sociodrama method is a method that is used to give understanding about social problems and also to develop students’ ability to solve the problems (Sanjaya, 2012). The writer intended to to this research to encourage students of SMPN 7 PPU to play roles some Indonesian National heroes hence they can understand how is the Indonesian Proclamation moment. The design of this study is Classroom Action research (CAR) that was conducted in SMPN 7 PPU. The subject in this study are the Eight grade students of SMPN 7 PPU. According to the result of the research, it can be concluded that conducting sociodrama method can enhance SMPN 7 PPU students’ PPKn learning result. It can be seen by the increasing of the mean score of the students from cycle 1, cycle 2 and cycle 3, which was 64.4% to 71.1% and 78%, which is above the standard, 71. This method can be considered as successful if 75% or more students pass the minimum score. In cycle 1, the students only watche their friends doing sociodrama, only 12.5% of students can pass the test. In cycle 2, half of students got involved in sociodrama and 50% of them got more than minimum score. The last, in the cycle 3, all of the students got involved in sociodrama and the percentage of students who passed the test is 87.5%.